Perforated Meckel's Diverticulum in an Adult - Camelo, R (2022)
Meckel's diverticulum is the commonest congenital anomaly of the gastrointestinal tract. Its complications have an extensive variety of clinical and imaging manifestations, extending from benign and indolent findings to acute life-threatening conditions. Complicated Meckel's diverticulum often constitutes a challenging diagnosis for both the clinician and the radiologist. Therefore, imaging techniques play an important role in this condition in evaluating its complications, determining decision making. We describe a case of a 49-year-old man suffering from right abdominal pain with fever and constipation, during the past 5 days. Laboratory data revealed C-reactive protein of 306 mg/L and leukocytosis. Contrast-enhanced CT features were highly suggestive of perforated Meckel's diverticulum. The purpose of this article is to emphasize that besides its rarity, Meckel's diverticulum complications can occur in adult patients.